A History of Self-Harm in Britain A Genealogy of Cutting and Overdosing - Millard, Chris (Springer Nature, 2015)
This book is the first account of self-harming behaviour in its proper historical and political context. The rise of self-cutting and overdosing in the 20th century is linked to the sweeping changes in mental and physical health, and wider political context. The welfare state, social work, Second World War, closure of the asylums, even the legalization of suicide, are all implicated in the prominence of self harm in Britain. The rise of 'overdosing as a cry for help' is linked to the integration of mental and physical healthcare, the NHS, and the change in the law on suicide and attempted suicide. The shift from overdosing to self-cutting as the most prominent 'self-damaging' behaviour is also explained, linked to changes in hospital organization and the wider rise of neoliberal politics. Appreciation of history and politics is vital to understanding the psychological concerns over these self-harming behaviours.